Nitroxide‐enhanced MRI of cardiovascular oxidative stress. (9th July 2020) - Shah, Soham A.; Cui, Sophia X.; Waters, Christopher D.; Sano, Soichi; Wang, Ying; Doviak, Heather; Leor, Jonathan; Walsh, Kenneth; French, Brent A.; Epstein, Frederick H.
Abstract : Background: In vivo imaging of oxidative stress can facilitate the understanding and treatment of cardiovascular diseases. We evaluated nitroxide‐enhanced MRI with 3‐carbamoyl‐proxyl (3CP) for the detection of myocardial oxidative stress. Methods: Three mouse models of cardiac oxidative stress were imaged, namely angiotensin II (Ang II) infusion, myocardial infarction (MI), and high‐fat high‐sucrose (HFHS) diet‐induced obesity (DIO). For the Ang II model, mice underwent MRI at baseline and after 7 days of Ang II ( n = 8) or saline infusion ( n = 8). For the MI model, mice underwent MRI at baseline ( n = 10) and at 1 ( n = 8), 4 ( n = 9), and 21 ( n = 8) days after MI. For the HFHS‐DIO model, mice underwent MRI at baseline ( n = 20) and 18 weeks ( n = 13) after diet initiation. The 3CP reduction rate, K red, computed using a tracer kinetic model, was used as a metric of oxidative stress. Dihydroethidium (DHE) staining of tissue sections was performed on Day 1 after MI. Results: For the Ang II model, K red was higher after 7 days of Ang II versus other groups ( p < 0.05). For the MI model, K red, in the infarct region was significantly elevated on Days 1 and 4 after MI ( p < 0.05), whereas K red in the noninfarcted region did not change after MI. DHE confirmed elevated oxidative stress in the infarct zone on Day 1 after MI. After 18 weeks of HFHS diet, K red was higher in mice after diet versus baseline ( p < 0.05). Conclusions: Nitroxide‐enhanced MRI noninvasively quantifies tissue oxidative stress as one component of a multiparametric preclinical MRI examination. These methods may facilitate investigations of oxidative stress in cardiovascular disease and related therapies. Abstract : In vivo imaging of oxidative stress can facilitate the understanding and treatment of cardiovascular diseases. We developed a kinetic model and evaluated dynamic nitroxide‐enhanced MRI for the detection of oxidative stress in mouse models of angiotensin II infusion (Ang II), myocardial infarction (MI), and diet‐induced obesity (DIO). The nitroxide reduction rate was elevated 7 days after Ang II, on Days 1 and 4 after MI, and 18 weeks after DIO, demonstrating that nitroxide‐enhanced MRI can quantify myocardial oxidative stress.